1996
DOI: 10.1016/s0022-5347(01)65636-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol on in Vivo Cystometry and in Vitro Whole Bladder Contractility in the Rat

Abstract: Ethanol significantly impairs detrusor contractility in the rat in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
1
13
0
4
Order By: Relevance
“…Elastic and easily expandable erectile tissue provides adequate compressive and stretching forces to drain the subtunical venules and cause high venous outflow resistance [18]. Changes in those structures may cause decreased relaxation of erectile tissue and affect the normal filling of the vascular spaces [19,20]. In our study we observed a significant decrease in the content of EF (p=0.002).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Elastic and easily expandable erectile tissue provides adequate compressive and stretching forces to drain the subtunical venules and cause high venous outflow resistance [18]. Changes in those structures may cause decreased relaxation of erectile tissue and affect the normal filling of the vascular spaces [19,20]. In our study we observed a significant decrease in the content of EF (p=0.002).…”
Section: Discussionsupporting
confidence: 53%
“…It is known that acute ethanol intoxication can cause urinary retention in benign prostatic hyperplasia [17]. In animal studies, the mechanism of urinary retention induced by ethanol partly showed that ethanol significantly impaired detrusor contractility in vivo and in vitro [18][19][20]. Several in vitro studies have revealed that ethanol had significant effect on both contractility and relaxation of rabbit corpus cavernosal smooth muscle (CCSM) [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that acute ethanol intoxication can cause urinary retention in patients with BPH [ 1, 2]. In animal studies, ethanol significantly impaired detrusor contractility in vivo and in vitro [ 2, 7]. The primary enzymatic steps in ethanol metabolism to acetaldehyde, acetate, CO 2 and water have been known for many decades but the implications of this for smooth muscle contractility have often not been recognised [ 4].…”
Section: Discussionmentioning
confidence: 99%
“…bilateraler Ligatur der A. iliaca interna bei Ratten zu induzieren, was zu gesteigerter Miktionsfrequenz, dem Auftreten von Detrusorhyperaktivitäten und Reduktion des maximalen Detrusordruckes führte [26]. [27,28]. Ursächlich werden Urothelschä-den, ein submuköses und intramuskulä-res Ödem sowie eine glattmuskuläre Degeneration beschrieben [26,27,28].…”
unclassified
“…[27,28]. Ursächlich werden Urothelschä-den, ein submuköses und intramuskulä-res Ödem sowie eine glattmuskuläre Degeneration beschrieben [26,27,28]. Die Blasenüberaktivität wird einer Neurodegeneration mit konsekutivem Anstieg des NGF zugeschrieben [26,29].…”
unclassified